Effect of chemical composition on the fusion behaviour of synthetic high-iron coal ash. (1st October 2019) - He, Chong; Bai, Jin; Ilyushechkin, Alexander; Zhao, Huiling; Kong, Lingxue; Li, Huaizhu; Bai, Zongqing; Guo, Zhenxing; Li, Wen
Highlights: A three-stage interpretation of ash fusion process is proposed. SiO2 /Al2 O3 benefits the formation of initial liquid phase in the second stage. The increasing CaO/(SiO2  + Al2 O3 ) reduces viscosity of liquid phase in the third stage. Flow temperature shows a negatively linear relationship with fusion heat. Abstract: High-iron coal is widely distributed throughout China and could be used as the feedstock for slagging gasifiers. To enable cleaner, efficient, large-scale use of high-iron coal by the slagging gasifier, a solid understanding of coal ash fusion behaviour is required. In this study, we investigated the fusion behaviour of synthetic high-iron coal ash (SiO2 -Al2 O3 -Fe2 O3 -CaO) using an ash fusion temperature (AFT) analyser, X-ray diffractometer (XRD), differential scanning calorimeter (DSC) and thermodynamic modelling. We found that AFTs decreased with increasing α values (CaO/(SiO2  + Al2 O3 ), mass ratio) due to the formation of low-melting-point minerals. AFTs also decreased with increasing S/A (SiO2 /Al2 O3, mass ratio), attributed to massive generation of the amorphous phase. The ash fusion process is described with three stages, namely, the mineral transformation, formation of the initial liquid phase, and melting of the residual solid phase. In the first stage, the mineral species was considered as the key parameter, and the increase in α and S/A favoured the formation of mineral with a low melting point. S/A also significantly influenced the second stage, with greater S/A ratios correlating with lower temperature and higher content of the initial liquid phase. In contrast, the third stage was accelerated by intense mass transfer, as the viscosity of the liquid phase dropped dramatically with increasing α value. The fusion heat corresponding to the melting of minerals at high temperature showed a negatively linear correlation with the flow temperature of synthetic coal ash, which may provide an alternative method of predicting the flow temperature of real coal ash.